The New Virtual Reality - Teachers' and Students' Perceptions and Experience in English Language Learning and Teaching Online - Milena, J. Tanasijević; Nataša, Z. Janković (University of Belgrade, Teacher Education Faculty, 2021)
An invisible, yet cruel virus has made the entire world face a new reality. Regardless of the degree to which online communication had already been used in educational settings before the Covid-19 pandemic, almost no one working in education had a feeling of being ready to work in the new circumstances. The process of migration to emergency remote language teaching and learning was stressful for all stakeholders in education - management, lecturers, students and their parents. Relying on the reflective and descriptive methods, the paper investigates the advantages and disadvantages of digital tools and platforms for remote collaborative learning, primarily ZOOM, Microsoft Teams, Jitsi Meet, and online learning management systems, recognised by the students and teachers within the mandatory and elective General English, ESP and EMI courses at the Teacher Education Faculty, University of Belgrade and Belgrade Metropolitan University. We conducted qualitative research by using structured and unstructured interviews and monitoring students' collaborative work. In the conclusion, the paper emphasises the aspects of educational technologies which have proved to be beneficial for everyone included in the process, without limiting the creativity, development of thinking skills and investigative spirit of students and lecturers while learning and teaching English.